RETHINKING THE PEDIGREES OF AFRICAN CULTURAL WATERSHED: A POST-COLONIAL INQUEST NTO CHINUA ACHEBE’S ARROW OF GOD - Montle, Malesela Edward (Institut Agama Islam Negeri Ponorogo, 2022)
The African cultural identities have undergone earth-shattering shifts from the precolonial epoch to the colonial and post-colonial periods. It is the colonial empire that advented in the African continent in the 15th century and attempted to erode and stigmatise African cultural practices as part of its mission to take control of Africa. Despite Africa being under a democratic administration today, African cultural identities are still marginalised, chiefly, by colonial remnants that have not yet been successfully uprooted. Thus, this paper aims to re-anatomise the African cultural identity-crises in the present day from the onset of colonialism on the continent. It utilises a qualitative approach and crystallises this African cultural watershed from a literary perspective. Chinua Achebe’s Arrow of God is purposively sampled for the paper as a primary reference point by dint of its conformity to the main theme of the study. The paper, comprehensively, blames the enduring colonial fragments in the present day for the African cultural identity-crises as they hinder decolonisation and peril African cultures. The colonial legacies in Africa today, like in the colonial times, are found to be championing Western identities at the expense of African cultural identities, hence, the latter is still menaced.